(untitled) (Nexo Revista Científica, 2021)
The principles of using light in choreographic performances are the basis of image perception integrity. The novelty of the study is determined by the fact that the illumination as a component of the performance can be based not only on the physical laws of light, but also on its imitation. To look into the matter of illumination, the authors consider it necessary to use a polygonal model, which can also form a spatial picture if necessary. The paper defines the general illumination model, which uses ray tracing technology and allows to determine the structure of lighting in the hall and to distribute the light to understand the director’s intention among the entire visual sector. The practical significance of the study is determined by the structure of using lighting as part of staging choreography in the postmodern genre.